Self-compassion: debunking happiness myth / Lee Phei Wei and Seng Hui Zanne - Lee, Phei Wei; Seng, Hui Zanne (Academy of Language Studies, 2022)
Scrolling through social media, seeing our friends share about their wonderful lives on the platform, and looking back at ourselves where we are probably feeling a mixture of emotions - amongst the mix, there may be a hint of criticism. As we focus on the smiles we see on the screen, we see how we are not doing so right now and believe that this is because we are defective. However, how true is this? The reality is, we as human beings experience a multitude of emotions just like the weather; sometimes it could be sunny and sometimes rainy, it's ever-changing and won't last forever. We may believe that in order to have a great life, we must and have to get rid of the unpleasant feelings. With how happiness and happy endings are depicted in movies, stories and social media postings, it looks nice on the surface - but looking back to the happiest moment of our lives, how long does the contentment last before we feel some other emotions?